2022
DOI: 10.1088/1748-9326/ac7889
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the lockdowns: satellite observations of aerosol optical depth through 2020, the first year of the COVID-19 pandemic

Abstract: Anticipated future reductions in aerosol emissions are expected to accelerate warming and substantially change precipitation characteristics. Therefore, it is vital to identify the existing patterns and possible future pathways of anthropogenic aerosol reductions. The COVID-19 pandemic prompted abrupt, global declines in transportation and industrial activities, providing opportunities to study the aerosol effects of pandemic-driven emissions changes. Here, measurements of aerosol optical depth (AOD) from two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 43 publications
3
1
0
Order By: Relevance
“…The main results indicate that AOD increased in the lockdown period and decreased in the post-lockdown period. This result is in line with Barragán et al [53] for the particular case of Madrid and with satellite studies that found an increase in AOD in the southwest of Europe during the 2020 lockdown [10][11][12][13].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The main results indicate that AOD increased in the lockdown period and decreased in the post-lockdown period. This result is in line with Barragán et al [53] for the particular case of Madrid and with satellite studies that found an increase in AOD in the southwest of Europe during the 2020 lockdown [10][11][12][13].…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, Ibrahim et al [11] analysed MODIS data over Europe and confirmed a 10% increase in AOD over Spain. This positive anomaly in AOD over Spain during March and April 2020 was also reported in the global studies performed by Sanap [12] and Smith et al [13] using MODIS and CALIPSO satellites.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations